DEMOTIVATIONAL FACTORS IN EFL CLASSROOMS: TEACHERS’ STRATEGIES & STUDENTS’ PERCEPTIONS AMONG NON-ENGLISH MAJOR - Kristiani, Isti; Haryanti, Ari Putri (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2025)
Motivation is the internal or external drive that pushes individuals to take action toward a goal, whereas demotivation refers to the loss or lack of interest, energy, or willingness to continue an activity or pursue a goal. In Indonesia, English is considered a foreign language, and many students struggle with speaking fluently due to various factors, including a lack of interest. This study aims to explore the processes that cause demotivation in English classes, as well as how teachers implement their strategies during the learning process. This study employed a mixed-method approach with convergent parallel design, integrating quantitative and qualitative data. The researcher collected the data by using questionnaires and interviews. The questionnaire provided quantitative data, while the interviews offered deeper qualitative insights. This study involved students from first-semester non-English major at the Islamic University of KH. Ruhiat Cipasung. The results indicated that although many students initially lacked interest in learning English due to their limited proficiency, the majority agreed that the teacher’s methods and strategies positively influenced their understanding of the material. Several students experienced increased motivation but some still showed minimal engagement. ABSTRAK Motivasi adalah dorongan internal atau eksternal yang mendorong seseorang untuk melakukan tindakan menuju suatu tujuan, sedangkan motivasi merujuk pada hilangnya atau kurangnya minat, energi, atau kemauan untuk melanjutkan suatu aktifitas atau mencapai tujuan. Di Indonesia, bahasa Inggris dianggap sebagai bahasa asing, dan banyak siswa kesulitan berbicara dengan lancar karena berbagai faktor, termasuk kurangnya minat. Penelitian ini bertujuan untuk mengeksplorasi proses yang menyebabkan demotivasi dalam kelas bahasa Inggris, serta bagaimana guru menerapkan strategi mereka dalam proses pembelajaran. Penelitian ini menggunakan metode campuran (mixed-method) dengan desain konvergen paralel, menggabungkan data kuantitatif dan kualitatif. Data dikumpulkan melalui kuesioner dan wawancara. Kuesioner memberikan data kuantitatif, sedangkan wawancara memberikan wawasan kualitatif yang lebih mendalam. Subjek penelitian ini adalah mahasiswa semester satu jurusan non-bahasa Inggris di Universitas Islam KH.Ruhiat Cipasung. Hasil penelitian menunjukkan bahwa meskipun banyak mahasiswa awalnya menunjukan sedikit minat dalam belajar bahasa Inggris karena kemampuan yang kurang, sebagian besar setuju bahwa metode dan strategi pengajaran guru berpengaruh positif terhadap pemahaman mereka terhadap materi. Beberapa siswa menunjukan peningkatan motivasi, meskipun sebagian dari mereka menunjukan keterlibatan yang kurang.